Tindak Pidana Korupsi Sebagai Kejahatan Korporasi - Burhanudin Burhanudin (Jurnal Cita Hukum, 2013)
Corruption as a Corporate Crime. In an effort to eradicate corruption in Indonesia has been conducted in various ways, however, the result is not satisfying because corruption is part of corporate crime which can be proven by the involvement of elite politician whether individually or in groups. The fight against corruption is still halfheartedly, moreover, the perpetrator does not seem to have to account for what he has done. DOI: 10.15408/jch.v1i1.2981